In silico characterization of the plastid proteomes of Chromera Velia and Vitrella brassicaformis - Faitová, Tereza (Jihočeská univerzita, 2018)
This thesis is focused on identification of the plastid proteome in alveolate algae C. velia and V. brassicaformis. Plastids play an important role in wide scale of biochemical processes. Therefore, targeting of involved enzymes with plastid targeting pre-sequences provide us with better view what function plastid has in the metabolism of chromerids and possibly of their close relatives. The first part of the thesis summarizes the current knowledge about alveolates, chromerids, endosymbiosis, and the principles of protein targeting. The second part describes the in silico analyses done in order to predict the plastid proteomes of both chromerid algae, to compare their plastid metabolism, and to determine the phylogenetic origin of nuclear-encoded plastid proteins.
In silico characterization of the plastid proteomes of Chromera Velia and Vitrella brassicaformis
In silico charakterizace plastidových proteomů u řas Chromera Velia a Vitrella brassicaformis
Keywords: Chromera velia; Vitrella brassicaformis; plastid proteome; protein targeting; apicomplexa; endosymbiosis